Evolving Frontiers: Mapping Current Trends in Business and Management Education in the 21st Century - Madegowda, J (International Journal of Education, Teaching, and Social Sciences, 2026)
In the 21st century, business and management education (BME) is undergoing a transformative shift. This is driven by globalization, rapid technological advancements, and evolving industry needs. This study explores the emerging trends that are reshaping the landscape of BME, mapping out key developments in curriculum design, pedagogy, and technological integration. It examines the transition from traditional to more dynamic, learner-centered approaches, with an emphasis on digital learning platforms, interdisciplinary courses, and the rise of entrepreneurial and soft skills training. It also highlights challenges such as the need for curriculum relevance, the integration of cutting-edge technologies, and the accessibility of BME across diverse demographics. Furthermore, by analyzing case studies of leading business schools, the study identifies best practices in aligning academic offerings with industry demands and preparing graduates for the future workforce. Furthermore, it discusses the implications for the future of BME, showing how institutions can balance tradition with innovation to meet the expectations of both students and employers. The findings provide valuable insights for educators, policymakers, and business school leaders as they navigate the evolving educational landscape in the era of digital transformation.